The Public Sphere: Liberal Modernity, Catholicism, Islam by Armando Salvatore (New York: Palgrave Macmillan, 2007. 293 pages.) (American Journal of Islam and Society, 2009)
A shortened version of his 2005 Habilitation thesis at Humboldt University,Berlin, this ambitious book both leans on and disagrees with German philosopherJürgenHabermas, the authoritative western theorist on the public sphereand communicative action. Salvatore applauds how Habermas created anoriginal synthesis between the idea of civil society developed in the Anglo-American tradition and the more radical version of “civic virtue” in theEuropean republican tradition emanating from Immanuel Kant. Habermashas masterfully wedded his theories of the public sphere and communicativeaction in such a way that “the only secure way to vindicate public reason isidentified with a democratic process” (p. 240).A great achievement, no doubt, but at what cost? Salvatore sees this theoryof the public sphere as condemned to an impasse. The “Habermas effect”has three main weaknesses: (1) it ultimately rests on the shaky ground of privatetrust; (2) its theory is limited to a western view of the self and citizenshipand, in the end, to the reach of a hegemonic western culture; and (3) thislimitation leaves out the all-pervasive dynamic of religious traditions in mostother parts of the world ...